The phylogeny of the species of the genus Agelaia Lepeletier, 1836, one of the basalmost groups of Epiponini, with notes on male genitalia (Hymenoptera: Vespidae; Polistinae) - Andena, Sergio R.; Noll, Fernando B. [UNESP]; Daza, Mario N.; Carpenter, James M. (American Museum of Natural History (BioOne sponsored), 2024)
A cladistic analysis of the species of the Neotropical social wasp genus Agelaia Lepeletier, 1836, was performed employing female morphology and nest architecture data. Analysis resulted in a single cladogram with length 339, consistency index 0.22, and retention index 0.60, supporting Agelaia as monophyletic. Agelaia bequaerti and A. anceps are raised to specific rank. Male genitalia of A. angulata, A. areata, A. cajennensis, A. centralis, A. flavipennis, A. fulvofasciata, A. multipicta, A. ornata, A. pallipes, A. panamaenis, A. testacea, A. timida, A. vicina, and A. yepocapa are depicted and described, including comparative remarks. A revised identification key is provided.